Microvessel density in the placental bed among preeclampsia patients - Coelho, Tarcisio Mota; Sass, Nelson; Camano, Luiz; Moron, Antonio Fernandes; Mattar, Rosiane; Stávale, João Noberto; Silva, Maria Regina Régis; Martins, Marília da Glória; Nogueira Neto, João; Mattar, Rosiane (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Morphological changes in the spiral arteries of the placental bed have been studied in patients with preeclamp- sia, one of the largest causes of maternal and perinatal morbidity and mortality. The reports show that vasospasm and vascular endothelial injury were two major pathological conditions for preeclampsia. The aim of this study was to investigate the microvessel density of spiral arteries in the placental bed, in pregnancies complicated by hypertension and proteinuria, and in normal pregnancies. DESIGN AND SETTING: This was a cross-sectional survey of immunohistochemical studies on biop- sies from the spiral arteries of the placental bed, among women undergoing cesarean sections for clinical and obstetrical reasons at Universidade Federal de São Paulo, São Paulo, Brazil. METHODS: Placental bed biopsies were obtained during cesarean section after placenta removal, with direct viewing of the central area of pla- centa insertion. The microvessel density of spiral arteries was measured by immunohistochemical methods in decidual and myometrial segments, using CD34 antibody. RESULTS: Biopsies containing spiral arteries were obtained from 34 hypertensive pregnant women with proteinuria, and 26 normotensive pregnant women. The microvessel densities in decidual and myometrial segments of the placental bed were compared between the groups. It was observed that, with increasing blood pressure and proteinuria, the microvessel density gradu- ally decreased. CONCLUSION: The presence of high levels of hypertension and proteinuria may be associ- ated with a progressive decrease in microvessel density in the placental bed.